2017
DOI: 10.1002/etc.3756
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of fungicides on leaf‐associated microorganisms and shredder populations—an artificial stream study

Abstract: Leaf litter is a major source of carbon and energy for stream food webs, while both leaf-decomposing microorganisms and macroinvertebrate leaf shredders can be affected by fungicides. Despite the potential for season-long fungicide exposure for these organisms, however, such chronic exposures have not yet been considered. Using an artificial stream facility, effects of a chronic (lasting up to 8 wk) exposure to a mixture of 5 fungicides (sum concentration 20 μg/L) on leaf-associated microorganisms and the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Our experiment showed that the fungicide impaired the survival of the common detritivorous insect Sericostoma pyrenaicum, matching previous results with detritivorous crustaceans such as Echinogammarus berilloni (Flores et al, 2014a) and Gammarus fossarum (Zubrod et al, 2014(Zubrod et al, , 2017. This is noteworthy because we used waterborne concentrations (0.125 and 1.25 μg L À 1 ) that were environmentally relevant and well below non-effect concentrations observed in chronic toxicity tests with microcrustacean daphnids (NOEC: 9 μg L À 1 ) (Elias and Bernot, 2014).…”
Section: Fungicide Exposure Leads To Lethal Effects On Invertebratessupporting
confidence: 91%
See 3 more Smart Citations
“…Our experiment showed that the fungicide impaired the survival of the common detritivorous insect Sericostoma pyrenaicum, matching previous results with detritivorous crustaceans such as Echinogammarus berilloni (Flores et al, 2014a) and Gammarus fossarum (Zubrod et al, 2014(Zubrod et al, , 2017. This is noteworthy because we used waterborne concentrations (0.125 and 1.25 μg L À 1 ) that were environmentally relevant and well below non-effect concentrations observed in chronic toxicity tests with microcrustacean daphnids (NOEC: 9 μg L À 1 ) (Elias and Bernot, 2014).…”
Section: Fungicide Exposure Leads To Lethal Effects On Invertebratessupporting
confidence: 91%
“…In our experiment, decomposition mediated by S. pyrenaicum was significantly reduced by exposure to chlorothalonil, in agreement with studies with Gammarus spp. (Dimitrov et al, 2014;Zubrod et al, 2014Zubrod et al, , 2017 and the caddisfly Chaetopteryx villosa Fabricius (Konschak et al, 2019) exposed to other fungicides, but contrasting with experiments finding no effects (Zubrod et al, 2011). The wide variety of fungicides and invertebrates used in experiments precludes any generalization currently.…”
Section: The Fungicide Reduces Litter Decompositionmentioning
confidence: 95%
See 2 more Smart Citations
“…In fact, fungicides induced a community shift by replacing aquatic hyphomycete species considered as palatable for leaf‐shredding detritivores (i.e., A. acuminata and T. angulatum ; Bärlocher & Kendrick, ; Arsuffi & Suberkropp, ; Graça, Maltby, & Calow, ; Bundschuh et al., ) with less palatable species (i.e., T. marchalianum and T. setigerum ; Bärlocher & Kendrick, ; Graça et al., ; Bundschuh et al., ). Consequently, an implication in the quality of leaves as food for leaf‐shredding detritivores is probable, with potential consequences for their life‐history strategy (Zubrod et al., ). However, leaf breakdown might be increased if fungicides and nutrient enrichment stimulate the abundance and biomass production of hyphomycetes preferred by leaf‐shredding detritivores (Zubrod, Feckler, et al., ).…”
Section: Discussionmentioning
confidence: 99%